Soil water tension and rice grain quality - Silva, Jaqueline Trombetta da (2019)
Due to the high water use in rice irrigation at the main producing regions of Brazil, it is necessary to test and develop new water-saving cropping systems. The alternate wetting and drying (AWD) system is promising in terms of maintaining productivity levels and water savings. In addition to grain yield, grain quality should be considered, as it is important for commercialization. This study aimed to evaluate the effect of moderate soil water deficiency at different phenological stages of three rice cultivars, on rice grain quality. The experiment was installed in randomized blocks design, with split‑plots and four replications. Treatments consisted on the following soil water levels (Factor B): (1) flooding; (2) saturated (0 kPa) but no flooding; (3) water tension up to 10 kPa; and (4) water tension up to 40 kPa. The crop developmental stage in which these water levels were applied was subdivided into three stages (Factor A): vegetative; reproductive initial and reproductive final. The whole, broken and streaked grains, chalky kernels and chalkiness were analyzed. There are no negative effects of water deficits up to 40 kPa applied to soil, at any phenological stage of rice, on grain quality of rice cultivar developed for continuous flood irrigation.